ANALISIS KEGUNAAN TUMBUHAN HERBA DI AREAL REKLAMASI PT ADARO INDONESIA KALIMANTAN SELATAN - Rukmawati, Rukmawati; Asy'ari, Mufidah; Rianawati, Fonny (Jurnal Sylva Scienteae, 2024)
Herbaceous plants are plants whose stems are not hard and woody. Herbs usually have soft stems and can live in wet places where other animals will not interfere with their growth. Herbs grow well under trees and in a variety of soil types and weather conditions. Herbaceous plants can also indicate how healthy the soil is. The purpose of this study is to Inventory understory plant species in the Reclamation Area of PT Adaro Indonesia South Kalimantan and Identify the use of understory plant species, especially herbs in the Reclamation Area of PT Adaro Indonesia South Kalimantan. The method used is using the literature study method. From the results of the study also obtained the type of utilization of the use of lower plants, especially herbs, the largest is for pharmacological use (78.4%), then followed by use as food (14.9%), animal feed (9.5%), ornamental plants / cover crop (9.5%), insecticides (8.1%), fertilizers (5.4%), crafts (2.7%), dyes (2.7%), cosmetics (5.4%), and other purposes (5.4%). Herba biasanya memiliki batang lunak dan dapat hidup di tempat basah di mana hewan lain tidak akan mengganggu pertumbuhannya. Herba tumbuh dengan baik di bawah pohon dan di berbagai jenis tanah dan kondisi cuaca. Tumbuhan herba juga dapat menunjukkan seberapa sehat tanah ditempat itu. Tujuan dari penelitian ini yaitu Menginventarisasi spesies tumbuhan bawah di Areal Reklamasi PT Adaro Indonesia Kalimantan Selatan serta Mengidentifikasi penggunaan spesies tumbuhan bawah terutama herba yang ada di Areal Reklamasi PT Adaro Indonesia Kalimantan Selatan. Metode yang digunakan yaitu menggunakan metode studi pustaka. Dari hasil penelitian juga didapatkan Jenis pemanfaatan penggunaan tumbuhan bawah terutama herba terbesar adalah untuk penggunaan farmakologis (78.4%), kemudian disusul untuk penggunaan sebagai pangan (14.9%), pakan ternak (9.5%), tanaman hias/cover crop (9.5%), insektisida (8.1%), pupuk (5.4%), kerajinan (2.7%), pewarna (2.7%), kosmetik (5.4%), dan keperluan lain (5.4%).